2021
DOI: 10.7554/elife.62448
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Mediterranean-type glucose-6-phosphate dehydrogenase deficiency against Plasmodium vivax malaria

Abstract: X-linked glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common human enzymopathy. The severe Mediterranean variant (G6PD Med) found across Europe and Asia is thought to confer protection against malaria, but its effect is unclear. We fitted a Bayesian statistical model to observed G6PD Med allele frequencies in 999 Pashtun patients presenting with acute Plasmodium vivax malaria and 1408 population controls. G6PD Med was associated with reductions in symptomatic P. vivax malaria incidence of 76… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The hypnozoites of P. ovale and P. vivax are responsible for the relapse of malaria infection months after complete treatment [ 59 , 60 ]. Primaquine (PQ) is the recommended antimalarial used for clearing these hypnozoites, however, PQ may cause haemolysis in G6PD deficient individuals [ 9 , 61 , 62 ]. Although some studies have reported the association between G6PDd A- variants and protection against P. vivax malaria [ 60 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypnozoites of P. ovale and P. vivax are responsible for the relapse of malaria infection months after complete treatment [ 59 , 60 ]. Primaquine (PQ) is the recommended antimalarial used for clearing these hypnozoites, however, PQ may cause haemolysis in G6PD deficient individuals [ 9 , 61 , 62 ]. Although some studies have reported the association between G6PDd A- variants and protection against P. vivax malaria [ 60 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protection offered by G6PDd A- against malaria infection is not well understood. It is unclear however, if both hemizygotes (A-) and heterozygotes (AA-) offer protection against severe malaria or bias towards females [ 9 , 22 ]. Although a recent case-control study conducted in Africa has reported a 46–58% reduced risk in severe malaria by both hemizygotes and heterozygotes G6PDd A- [ 23 ] and heterozygotes G6PDd A- but not hemizygotes G6PDd A- has been reported to protect against acute malaria among children in Nigeria, suggesting sex-specific malaria protection [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…G6PDd is among the inherited blood disorders believed to have been selected by survival advantages against endemic malaria [ 54 57 , 103 , 104 ]. As already explained, P .…”
Section: Introductionmentioning
confidence: 99%
“…G6PD testing has not been made widely available and so the possibility of doing harm by causing oxidant haemolysis has markedly limited implementation of radical cure [11,12]. Individual and population risks associated with primaquine radical cure have not been defined well, particularly as G6PD deficiency protects against P. vivax malaria [13], nor has the cumulative adverse impact of not providing radical cure (i.e., the burden of relapse). However, mainly because of tafenoquine, more than a decade of recent development has resulted recently in marketing of the first point-of-care biosensors, which allow a quantitative measurement of G6PD activity [14][15][16].…”
mentioning
confidence: 99%